Is visual art relevant in medical school buildings? - Ballal, Apoorva; Shetty, Ashalatha (Research and Humanities in Medical Education, 2019)
Aim: The aim of this project was to determine if visual art serves a purpose in medical teaching establishments, particularly in hospitals and medical schools, or if it is largely invisible. Methods: After a literature review revealed a lack of robust or extensive evidence on the effects of displayed art in buildings that comprised medical schools, a questionnaire was distributed opportunistically to the students attending lectures or clinical skills training and to the staff at their offices in the Aberdeen University Medical School. The questionnaire sought to evaluate the effect of the art installed at the newly built Suttie Centre, an integral building of the Aberdeen University Medical School, on staff and students using the building. Results: Of 75 questionnaires distributed, 52 were returned complete in all respects. Most respondents agreed that the artwork was appropriate and aesthetically pleasing for the medical school, and helped enhance the ethos of learning. Conclusion: The literature review, though scanty evidence is available, is backed by questionnaire responses to show that art serves to epitomize the ethos of a medical institution. A medical school with a ’soulless environment’ is less likely to enable students and staff to learn and work to their best potential. Subjective opinions regarding which artworks to display and qualms about the costing of artwork and prioritization of money must be considered; however, overall, visual art seems to have a place in medical school buildings.